2020
DOI: 10.2147/cmar.s258584
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synergistic Effects of Resveratrol and Temozolomide Against Glioblastoma Cells: Underlying Mechanism and Therapeutic Implications</p>

Abstract: Purpose Temozolomide (TMZ) is a commonly used anti-glioblastoma (GBM) drug. However, glioblastoma cells frequently show primary and acquired resistance to TMZ. As a promising anti-GBM candidate, resveratrol (Res) faces the similar problem as TMZ. Although resveratrol combined with TMZ (Res/TMZ) has been reported to be used to treat GBMs, it remains unclear whether this combination is broad-spectrum for all glioma cells until now, especially for GBM cells/cases with dual drug resistance. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…Furthermore, some studies have reported that the use of resveratrol can enhance chemotherapy-induced apoptosis in glioblastoma cell lines. The mechanisms would be either increased expression levels of apoptotic factors such as p53, BAX and caspase 3 or decreased expression levels of anti-apoptotic factors such as NF-κB and BCL-2 [ 119 122 ]. Li et al reported that temozolomide-induced apoptosis in glioblastoma-initiating cells is enhanced by resveratrol through DNA double-stranded breaks (DSBs)/pATM/pATR/p53 pathway activation [ 119 ].…”
Section: Role Of Resveratrol In Glioblastoma Treatmentmentioning
confidence: 99%
“…Furthermore, some studies have reported that the use of resveratrol can enhance chemotherapy-induced apoptosis in glioblastoma cell lines. The mechanisms would be either increased expression levels of apoptotic factors such as p53, BAX and caspase 3 or decreased expression levels of anti-apoptotic factors such as NF-κB and BCL-2 [ 119 122 ]. Li et al reported that temozolomide-induced apoptosis in glioblastoma-initiating cells is enhanced by resveratrol through DNA double-stranded breaks (DSBs)/pATM/pATR/p53 pathway activation [ 119 ].…”
Section: Role Of Resveratrol In Glioblastoma Treatmentmentioning
confidence: 99%
“…Resveratrol (3,4′,5-trihydroxy-trans-stilbene) anti-cancer effects include anti-proliferation, cell cycle arrestment, and apoptosis promotion through multiple signaling pathways such as EGFR, p53, P13K/AKT/mTOR, STAT3, NF-κB, and oncogenic miRNAs [ 296 , 297 ]. Resveratrol suppresses tumor growth and prolongs survival in rats bearing intracranial C6 glioma [ 296 , 298 , 299 ].…”
Section: Phytochemicals and Nanoparticles In Hggmentioning
confidence: 99%
“…Resveratrol administration decreased the expression of EGFR, MMP-9 NF-κB, PCNA, COX-2, and VEGF while increasing GFAP expression compared to the control group. Resveratrol also enhances Tmz efficacy by reducing ROS/ERK-mediated autophagy and promoting apoptosis [ 297 , 299 , 300 ]. Resveratrol in combination with Tmz suppresses the cell growth and induces apoptosis in RG-2 cell (>20%, 17%), LN-18 (62.3%, 12%), and LN-428 cells (28.6%, 8%) [ 297 ].…”
Section: Phytochemicals and Nanoparticles In Hggmentioning
confidence: 99%
See 2 more Smart Citations